Bokanmeldelse: Birgit Weyel, Wilhelm Gräb, Emmanuel Lartey and Cas Wepener (eds.). International Handbook of Practical Theology - Saxegaard, Fredrik; Kaufman, Tone Stangeland; Austad, Anne; Stene, Valborg Orset; Westly, Inge (Tidsskrift for Praktisk Teologi, 2023)
Book review: Birgit Weyel, Wilhelm Gräb, Emmanuel Lartey and Cas Wepener (eds.). International Handbook of Practical Theology.